Humanitarian Policies and Natural Disasters in the European Union: the strengths and limitations of legislation - Abdon de Paula; Judite Gonçalves de Freitas (População e Sociedade)
In the last few decades, the European Union (EU) has developed a comprehensive approach to natural disaster management, with a particular focus on civil protection laws and international cooperation. The EU acknowledges the importance of proactive measures to minimize the impact of potential crises, namely in the context of climate change, in response of the increasing complexity and frequency of climate-induced disasters. This study analyses and discusses EU humanitarian legislation that aims to promote disaster resilience in member states. It starts with an overview of the EU’s legal framework, continuing with an analysis of the different types of secondary legislation in the Union, distinguishing their purposes and respective attributes, and then delves into the already established bases for preventing and mitigating the impacts of natural disasters and the frequency of such risks. Finally, a critical reflection is made on the strengths and limitations of the legal basis established by the EU.